Tingkat Kepuasan Pelanggan dan Strategi Pengembangan Usaha Jasa Salon Kecantikan Keraton di Tangerang - Wine Widiana; Musa Hubeis; Sapta Raharja (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
Salon Kecantikan Keraton that was  established in 2007 is  required to improve services in order to compete in facing the competition of growing salon business. Since Salon Kecantikan Keraton was established, there is a number of customers decreased significantly, so the researcher is trying to conduct a study  in order to increase the number of customers and increase the  profitability of the Salon Keraton. The methods used in this research are descriptive analysis, reliability and validity test, chi-square, cross tabulation, IPA, CSI and SWOT analysis. Customer characteristics of Salon Kecantikan Keraton majority are women aged 26-35 years worked as employees whose income of Rp1-3 million. In general,  customers  get information from the banner that is placed in front of the salon. Based on the relationship between customers and the level of performance characteristics can be concluded that female customers, especially those who are  over the age of 40 years and customers who have income above Rp8 million more sensitive and requires more attention to handle.Employee and entrepreneur are easier to understand and comprehend the type of care provided, the frequency of visits depends on the services during the first visit can lead to good impression on customers, sources of information with a banner that is placed in front of the Salon Kecantikan Keraton’s staff are very helpful in providing information the type of care and price of Salon Kecantikan Keraton. The main priority of repairs need to be done about strategic accelerate Salon Kecantikan Keraton performance repaired relevate with cost and benefit and Salon Kecantikan can achieve optimum goals and easy for implementation.